2017
DOI: 10.1038/srep45300
|View full text |Cite
|
Sign up to set email alerts
|

The role of CREB3L4 in the proliferation of prostate cancer cells

Abstract: The incidence of prostate cancer (PC) is growing rapidly throughout the world, in probable association with the adoption of western style diets. Thus, understanding the molecular pathways triggering the development of PC is crucial for both its prevention and treatment. Here, we investigated the role of the metabolism-associated protein, CREB3L4, in the proliferation of PC cells. CREB3L4 was upregulated by the synthetic androgen, R1881, in LNCaP PC cells (an androgen-dependent cell line). Knockdown of CREB3L4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
(39 reference statements)
0
31
0
Order By: Relevance
“…CREB3L4 is a principal correlated gene (Fig. 7A) that is abundantly expressed in prostate and breast cancer cell lines (43–45). Regression analysis revealed that MUC1 and CREB3L4 had high relevant coefficients (Spearman's correlation=0.60; Pearson's correlation=0.54) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CREB3L4 is a principal correlated gene (Fig. 7A) that is abundantly expressed in prostate and breast cancer cell lines (43–45). Regression analysis revealed that MUC1 and CREB3L4 had high relevant coefficients (Spearman's correlation=0.60; Pearson's correlation=0.54) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HPGD is positively regulated by the androgen receptor (AR) (26) and that the AR is expressed by HL-1 cardiomyocytes (27). We observed that HPGD expression was significantly lower in control HL-1-STAT3-KD-CM compared to HL-1-ctrl-CM (Figs 2F and 2H).…”
Section: Resultsmentioning
confidence: 99%
“…In this context it has been shown that the AR can be activated by different ligands including interleukin (IL)-6 and testosterone (37). The AR is expressed in cardiomyocytes from various species including mouse and human (26, 38, 39) and STAT3 acts as a positive co-factor for AR signaling by directly interacting with amino acids 234-558 in the N-terminal domain of the AR (24). The AR is expressed on HL-1 cells and indeed, HPGD expression is lower in HL-1-STAT3-KD-CM compared to ctrl HL-1-CM.…”
Section: Discussionmentioning
confidence: 99%
“…As is typical of other ATF/CREB proteins, CREB3L4 contains a bZIP domain, which is located in its central region (amino acids 222-280). In humans, CREB3L4 is highly expressed in a variety of cancer types, including prostate carcinomas [11,19,20], hepatocellular carcinomas [21] and endometrial cancers [13]. Recently, it was revealed that the high messenger RNA (mRNA) expression of CREB3L4 was associated with reduced relapse-free survival (RFS) and diseasespecific survival (DSS) in BC [22].…”
Section: Introductionmentioning
confidence: 99%